Effect of elite physical exercise by triathletes on seven catabolites of DNA oxidation. (August 2015) - Villaño, D.; Vilaplana, C.; Medina, S.; Cejuela-Anta, R.; Martínez-Sanz, J. M.; Gil, P.; Genieser, H.-G.; Ferreres, F.; Gil-Izquierdo, A.
Abstract: The oxidized nucleoside 8-hydroxy-2'-deoxyguanosine has been widely studied as a marker of DNA oxidation; however, data on the occurrence of other metabolites in plasma that are related to DNA damage are scarce. We have applied an improved, sensitive, robust, and reliable method, involving solid phase extraction and ultrahigh-performance liquid chromatography (UHPLC)–tandem mass spectrometry (MS/MS), to the precise quantitation of seven metabolites in the plasma of 15 elite triathletes after a 2-week training program. All compounds were eluted in the first 1.6 min, with limits of detection and quantification ranging between 0.001 and 0.3 ng.mL −1 and 0.009 and 0.6 ng.mL −1, respectively. Four compounds were detected in plasma: guanosine-3'-5'-cyclic monophosphate, 8-hydroxyguanine, 8-hydroxy-2'-deoxyguanosine, and 8-nitroguanosine. After two weeks of training, 8-hydroxyguanine exhibited the highest increase (from 0.031 ± 0.008 nM to 0.036 ± 0.012 nM) ( p < 0.05), which could be related to the enhanced activity of DNA-repairing enzymes that excise this oxidized base. Increased levels of guanosine-3'-5'-cyclic monophosphate and 8-hydroxy-2'-deoxyguanosine were also observed. In contrast, levels of 8-nitroguanosine ( p < 0.05) were significantly reduced, which might be a protective measure as this compound strongly stimulates the generation of superoxide radicals, and its excess is related to pathologies such as microbial (viral) infections and other inflammatory and degenerative disorders. The results obtained indicate an induced adaptive response to the increased oxidative stress related to elite training, and point to the benefits associated with regular exercise.